Potential production and loss rates of picocyanobacteria in tropical coastal waters - Pei, L.H.; Choon, W.L. (2012)
In this study, monthly samplings were conducted at Port Klang and Port Dickson over a two-year period to measure potential production rate and loss rates of picocyanobacteria using the Landry Hassett dilution technique. Twelve sets of two-factorial experiment were also carried out to further investigate the effect of light and nutrient on picocyanobacteria production rate. Significantly lower abundance was measured at Port Klang (2.80 ± .172 x 104 cell rnl") compared to Port Dickson (13.2 ± 4.68 x 104 cell ml') (Student's z-test: I = 9.80, df= 40, P < 0.001). Potential production and loss rates observed at Port Klang (3.77 - 70.4 and 1.88 - 75.60 x 102 cell ml' hOi)were also much lower than Port Dickson (2.32 - 15.90 and 1.06 - 18.4 x 103cell ml" hOi)(Student's 1-test: 1= 9.63, df= 37, P < 0.001; 1= 7.49, df= 43, P < 0.001). In the twofactorial experiment, only nutrient (F = 7.00, P < 0.05) showed a significant effect on production rate. However, the interaction between light and nutrient also have a significant effect on production rate (F = 5.80, P > 0.05). These results suggest that in tropical coastal waters, nutrient played a more important role in affecting the picocyanobacteria production rate compared to light.